Development of rehabilitation services in an Inuit sociocultural context: challenges, strategies and considerations for the future. Issue 1 (31st December 2022) - Ouellet, Lauriane; Grandisson, Marie; Fletcher, Christopher
ABSTRACT: In recent years, a new rehabilitation programme has been developed on the Hudson Bay coast of Nunavik. The purpose of this article is to reflect on the experience of an occupational and physical therapy programme development in an Inuit sociocultural context. To do so, the challenges encountered during the first years following the implementation of rehabilitation services and the strategies implemented by the professionals to overcome them were identified, examined in the light of the literature, and discussed with members of the rehabilitation team. The challenges encountered and strategies implemented were divided into 10 major themes: (1) diverse clinical needs; (2) communication issues; (3) acquisition of cross-cultural interaction and population-specific knowledge; (4) adaptation of clinical practice to Nunavimmiut; (5) client engagement in rehabilitation; (6) professional isolation; (7) lack of awareness around the objectives and scope of rehabilitation practice; (8) use of culturally safe assessment tools; (9) staff turnover; (10) large geographic area to be served. This exercise highlighted the need to adapt clinical rehabilitation practices to Nunavimmiut's worldviews and culture, as well as to adopt a reflective practice in order to improve the quality, relevance and effectiveness of rehabilitation services.